A sulfonated polyvinyl alcohol ionomer membrane favoring smooth electrodeposition of zinc for aqueous rechargeable zinc metal batteries. Issue 21 (4th October 2021) - Vijayakumar, Vidyanand; Torris, Arun; Kurian, Maria; Mathew, Megha Mary; Ghosh, Meena; Khairnar, Ajay B.; Badiger, Manohar V.; Kurungot, Sreekumar
Abstract : Sulfonated polyvinyl alcohol ionomer membrane for aqueous rechargeable zinc-metal batteries shows its superiority over the non-ionomer counterpart, ensuring smooth Zn electrodeposition and better cycling stability in MnO2 ‖Zn cells. Abstract : One of the failure mechanisms of aqueous rechargeable zinc metal batteries (AZMBs) involves high surface area zinc (HSAZ)/dendrite-like deposits over the Zn-metal anode during long-term cycling. Negatively charged (anionic) polymeric ionomer electrolyte membranes and separators are known for suppressing the dendrite-/HSAZ-induced failure of AZMBs. However, the preparation of cost-effective and non-fluorinated ionomers from cheap and environmentally friendly polymers is essential to leverage the feasibility of AZMBs. The current work demonstrates the potential of an ionomer electrolyte membrane (P-AS-C-Zn) made by the crystallization-induced physical cross-linking of sulfonated poly (vinyl alcohol) (PVS) and poly (vinyl alcohol) (PVA) as a dendrite-/HSAZ-inhibiting separator for AZMBs. The P-AS-C-Zn membranes exhibited excellent Zn plating/stripping behavior with a stable voltage vs. time profile beyond 1100 h, compared to their neutral PVA-C-Zn counterpart without any ionomer character (cell failure at close to 280 h). Applying the optimized P-AS-C-Zn membrane in a MnO2 ‖Zn full cell helps retain about 50% of the initial capacity close to 600 cycles in the absence of extra manganese salt in the electrolyte, which is indeed promising.